Pengembangan Instrumen Evaluasi Maharah Kitabah - Vivi Miftahul Jannah,; Ummu Salamah,; Ubaid Ridlo, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Maharah kitabah is an important language skill in Arabic language learning as it requires active and productive language mastery. This article aims to examine the urgency of maharah kitabah, its levels of learning, and the forms of evaluation instruments that can be used to assess Arabic writing skills. This study employs a descriptive qualitative approach using a library research method through the analysis of relevant literature sources. The findings indicate that the teaching of maharah kitabah should be conducted in stages, from the basic to the advanced level, and evaluated using instruments that include mechanical writing, guided writing, and free writing in order to measure students’ writing abilities comprehensively.